Medical Migration: a review on the licensing process for International Medical Graduates in Australia and other destinations - Malek, Sharafat; Talukder, Md Humayun Kabir (Bangladesh Journal of Medical Education, 2018)
Movement of health care professionals, nationally or internationally, has now become a common trend worldwide. International recruitment of efficient physicians is an ongoing process for years although some studies have identified this culture as an issue.10-11 Waves of migration to popularly Australia under ‘Skilled Migration’ and other categories started in Bangladesh in early 1970, which have been ongoing since then.1 Among over thirty thousands of such migrants living in the popularly Australian States2; the medical graduates from Bangladesh are identified through their associations/forum made in each State as well as from the data on their participation in the re-accreditation examinations.3-4, 7-8 A lack of pre-migration awareness on social and academic barriers in the host country has been found far more common in the Australian International Medical Graduates’ (IMGs) studies published before 20045. Poor knowledge on the hurdles may affect IMGs’ post-migration coping or adjustment process. Fortunately, internet facilities are widely available so, modern IMGs no more need to rely on information from relatives, friends or high commission/embassy people. Yet, full access to career and job related journals could still be out of reach for many IMGs. Updated clear knowledge around licenselegislation at the destination would help IMGs gaining smoother transition whilst preparing to build the same career, albeit in a different system. This review article at first presents the background behind strict regulations on permitting the IMGs to practise in major destinations. It then progresses with reviewing these regulations in the developed countries including Australia. Following that a detailed summary has been made on the Australian regulations. Available literature6-8 demonstrates a large discrepancy between IMGs’ success rates in the knowledge and practical part of the licensing (Australian Medical Council) process (i.e. 80% vs. 42% in case of Bangladeshi-IMGs). Therefore, this paper has properly discussed the nature and structure of the practical (AMC-Clinical) examination incorporating examples. Useful web-links on Australian IMGs’ accreditation preparation, permanent migration and finding medical jobs have been provided at relevant sections. Finally, a recommendation has been made to teach 3rd-year medical students on this important area under the ‘Community Medicine’ curriculum in Bangladesh. Bangladesh Journal of Medical Education Vol.9(1) 2018: 26-34